Landscape as Connecting Link of Nature and Culture: Spatial Planning Policy Implications in Greece - Stella Sofia Kyvelou; Anestis Gourgiotis (Urban Science, 2019)
The research paper investigates the diverse understandings of “landscape”, along with demonstrating the modes of contribution of the European Landscape Convention (ELC) of the Council of Europe (CE) in influencing national spatial planning systems. The paper, interested in considering the efficiency of landscape policy from a territorial perspective, briefly outlines the perception and understanding of landscape as connecting link of nature and culture and conducts a literature review with the aim to support the prospect of a «European model of landscape planning». Lastly, it critically examines the approach to landscape planning and management by the Greek state, revealing the catalytic role of the Council of Europe (CE) in activating the dimension of landscape in Greece, in a mutualistic perspective between environmental policy and spatial planning, mainly through strategic spatial planning tools (i.e., the Regional Spatial Plans, RSPs). The results point out that (a) the ELC gave new impetus to spatial planning in Greece, providing the tool to manage and coordinate landscape policy, positively influencing the evolving spatial planning paradigm; (b) the decentralized approach adopted, identified landscapes of particular value at a regional level, so as to be given priority in terms of the implementation of coordinated governance arrangements and management actions. However, the implementation of landscape policy continues to rely on the underlying spatial planning level (Local Spatial Plans, Special Spatial Plans) and a general conclusion is that both on land and on sea, it depends on the incorporation of evolutionary trends in planning including an evolutionary perspective for landscape itself, viewed as a complex social-ecological system.